Preliminary correlation analysis reveals the relationship between ginsenosides in multi stem ginseng and soil properties - Xu, Zhefeng; Chen, Yuqiu; Xue, Yan; Zhang, Kemeng; Yang, Ruixue; Wang, Yibing; Sui, Jiahong; Sun, Yingmei; Fang, Jing; Zhang, Qinghe; Chen, Changbao; Zhang, Tao (Frontiers in Soil Science, 2026)
Compared with single stem ginseng (SSG), there is less research on the natural formation and quality of multi stem ginseng (MSG). This research measured the ginsenoside content in the roots, stems, and leaves of 4-year-old SSG, double stem ginseng (DSG), and triple stem ginseng (TSG), as well as the endogenous hormone content in the rhizomes. At the same time, the physicochemical properties and enzyme activity of the rhizosphere and non-rhizosphere soil were measured, and the differences and connections between each indicator were analyzed. The results showed significant differences in the content of ginsenosides and endogenous hormones between SSG and MSG. TSG had the highest content of ginsenosides in roots, DSG had higher content of ginsenosides in leaves, and SSG had the highest content of salicylic acid and brassinolide in rhizomes than MSG. The activities of trace elements (Ce, Nd, Pr, La, Y, Tb, Fe, Mn) and phosphorus cycling enzymes (ribonuclease, acid phosphatase, phytase) in the rhizosphere soil of TSG were significantly highest. In addition, Pr, Nd, and Ce might affect the morphological construction of TSG by influencing the accumulation of brassinolide in TSG. Finally, we found that Ce, Pr, Zn, and β-amylase significantly affect the accumulation of ginsenosides. Overall, compared to SSG, MSG undoubtedly has higher medicinal and economic value, and soil rare earth elements may play a more critical role in the formation of MSG morphology and quality.